(untitled) (Global Conference on Medical and Health Sciences, 2026)
Cognitive decline, encompassing conditions such as mild cognitive impairment (MCI) and early-stage dementia, represents a growing global health challenge due to aging populations and increasing life expectancy. Early detection of cognitive impairment is essential for timely intervention and improved patient outcomes; however, conventional diagnostic approaches often rely on clinical assessments and neuroimaging techniques that may fail to detect subtle functional changes in the brain. In this context, electrophysiological biomarkers, particularly those derived from electroencephalography (EEG) and event-related potentials (ERPs), have emerged as promising tools for the early identification of cognitive decline.